(untitled) (Hilo Analítico, 2025)
In this research exercise, a skin test was carried out on first semester participants of the Antonio Nariño University, where the results showed that the participants on average perceived stimuli of higher intensity on the skin and did not receive stimuli of lower intensity, which is related to the concept of absolute thresholds. It was also identified that this result was influenced by the “attention filter”.